(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the development of estrada music in Uzbekistan, its formation, founders, and its current relevance. It traces the evolution of estrada music from the 1950s, highlighting the contributions of pioneers such as Botir Zokirov and Enmark Salikhov and their influence on the genre’s growth. The article discusses the primary trends in estrada music, the creation of orchestral ensembles, the emergence of bit music, and the significant role of young singers and the new generation of artists. It also analyzes the unique characteristics of traditional folk music and its impact on the development of estrada art.